Dynamics of polymers in concentrated solutions: A weaker self-concentration effect. (26th September 2018) - Yan, Zhi-Chao; Wang, Wei
Abstract: We examine the validity of the Lodge-McLeish (LM) self-concentration model on polymer dynamics in concentrated polymer/small molecule solutions. Three solutions, 1, 2-polybutadiene/2-ethylhexyl benzoate, 1, 4-polyisoprene/phenyloctane, and polystyrene/2-ethylhexyl benzoate, are investigated by rheological technique. The temperature dependence of their normalized terminal relaxation times is fitted by the WLF equation to extract the effective glass transition temperature. The calculated self-concentration is found lower than the LM prediction, in contrast with the significant values in miscible polymer blends. According to the molecular dynamic simulation, this weak self-concentration effect is explained by the overestimation of the polymer's interchain concentration, which is postulated as the global average concentration in the original LM model. The lower interchain concentration in solutions is attributed to the higher probabilities for small molecules to fill the cooperative volume. Both experimental and simulation results may motivate the further theoretical modification on the interchain concentration in order to establish a self-consistent model predicting both miscible blends and polymer solutions. Graphical abstract: Left: The effective glass transition temperature of polystyrene (PS) in tricresyl phosphate (TCP) solutions measured by diverse techniques. The solid curve is the best fitting by the Fox equation with a self-concentration ϕ self = 0, while the dashed curve is the fitting using a Lodge-McLeish predicted self-concentration ϕ self = 0.27. Right: A cartoon illustrating that the space around a Kuhn segment is preferentially occupied by small molecule solvent rather than other polymers in polymer solutions. As a result, the interchain concentration ϕ m is smaller than the global average concentration ϕ ave . Image 1 Highlights: A weaker self-concentration effect in concentrated polymer solutions. The universally weak self-concentration in different polymer solutions and techniques. The interchain contribution is responsible for the weak self-concentration effect. Invalidity of Lodge-McLeish model in polymer solutions.